Study of Educational Motivation among Agricultural Managers - Zalainé Piros, Márta (Acta Agraria Debreceniensis, 2002)
It is a priority for companies to utilise human resources as much as possible. The form and effectiveness of the utilisation of labour largely depends on how much the manager of the company and the human resource management area support and encourage labour to develop individually and work more efficiently – as far as the size of the company justifies and allows. Effective incentive methods have to be set and run. Training incentives will have to play an important part in the future.There has been no major difference between training incentives between managers and subordinates. Material incentives continue to be the key factor. For managers, exchange of information is currently a primary training incentive, as is the opportunity to meet other experts and exchange their ideas. Further, performance-related payment and bonuses applied jointly are also some material incentives. In the future, material incentives will gain in importance. For subordinates, the operation of material incentives is currently highly important as a training incentive. This is not expected to change in the future either, while expectations linked to quality work will strengthen.